The victim's experience of hijacking: an exploratory study - J Macgregor; WJ Schoeman; AD Stuart (AOSIS, 2002)
This paper summarises a phenomenological study that was designed to explore the victim's lived experience of undergoing a motor vehicle hijacking. Opsomming Hierdie artikel verskaf 'n oorsig oor 'n fenomenologiese studio wat ontwerp is om die slagofferse geleefde ervaring van 'n motorkaping te ondersoek. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.